(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
India in the 19th century looked like a shadow of a once vibrant civilization. Politically, it was a period of servility, intellectually, a period of blind imitation of the west and spiritually, a time of confusion and despair. The country struggled under a crushing load of unreason, in abject slavery to circumstances. Indian society was steeped in superstitious, obsolescent rituals and prejudices. Since the beginning of the 19t h century there have been many socio-religious reform movements in India but Haryana remained almost unaffected by them. However, Arya Samaj took the region into its fold. I t made untiring efforts to raise the socio-religious status of agricultural communities, to spread education, remove untouchability and to raise the social status of women.